2x^2+9x-5=0
D=b^2-4ac=9^2-4*2(-5)=81+40=121 -корень-11
x1,2= -b+\-корень из D / 2a= -9+\-11 / 4= -5 ; 0,5
(х+3)(5х-3)=05x^2+12x-9=0
D=k^2-ac=6^2-5*(-9)=36+45=81 -корень-9
x1,2= -k+\-корень из D / a= -6+\-9 / 5= -3 ; 0,6
(4у-3)(5-8у) =0-32y^2+44y-15=0 | *(-1) __ 32y^2-44y+15=0
D=k^2-ac=(-22)^2-32*15=484-480=4 -корень-2
x1,2= -k+\-корень из D / a= 22+\-2 / 32= 0,625 ; 0,75
(6а+5)(а-8)=06a^2-43a-40=0
D=b^2-4ac=(-43)^2-4*6(-40)=1849+960=2809 -корень-53
x1,2= -b+\-корень из D / 2a=43+\-53 / 12= -5\6 ; 8
10+21>10a+9
21>9 верно
(а-5) (а+9) < (а-4) (а+8)
a²-5a+9a-45<a²-4a+8a-32
4a-45<4a-32
-13<0 верно
(а-13) (а-2) < (a-12) (a-3)
a²-13a-2a+26<a²-12a-3a+36
-15a+26<-15a+36
26<36 верно
(a-11) (a-3) < (a-10) (a-4)
a²-11a-3a+33<a²-10a-4a+40
-14a+33<-14a+40
33<40 верно